Potential of various trap crops for the control of Bemisia tabaci on chilli pepper - Mihwan Sataral; Syahril Daud; Fahri; Maria Hevianti (Faculty of Agriculture, Tompotika Luwuk University, 2022)
The whitefly Bemisia tabaci is an important pest of chilli peppers and a vector insect that causes yellow leaf disease. This study aimed to compare the whitefly population and the intensity of its attacks on chilli production in plots with or without trap crops. This study used eggplant, tomato and mungbean as trap crops. As the main crop, Chilli pepper was planted in plots measuring 7 m x 4 m with a spacing of 60 cm x 70 cm. Trap crops were planted around the chilli pepper plots, with 16 plants in each plot. The results showed a significant difference between whitefly populations and the intensity of their attacks in plots without trap crops and plots with mungbean traps. The biggest chilli weight was obtained from plots with mungbean trap plants. State that mungbean has the best potential as a trap crop to control B. tabaci.